Modulation of inflammatory changes in the rat hippocampus by atorvastatin - Clarke, Rachael M. (Trinity College (Dublin, Ireland). Department of Physiology, 2007)
Inflammatory changes, typified by an increase in pro-inflammatory cytokine production and upregulation of corresponding signalling pathways, have been consistently shown in the brain of aged animals and animals treated with agents which induce inflammatory stress, like LPS or Aβ. These changes have been coupled with a deficit in LTP in the hippocampus. One response of the brain to stressors is to increase microglial activation with the consequent production of pro-inflammatory cytokines such as IL-1β with downstream consequences including activation of the MAP kinase and NFκβ signalling pathways. The evidence suggests that anti-inflammatory agents which attenuate the stress-induced and age-associated increases in hippocampal cytokine concentration lead to restoration of LTP. The aim of this study was to establish whether the stress-induced inhibition of LTP in perforant path-granule cell synapses, was coupled with evidence of microglial activation and pro-inflammatory signalling and to assess whether atorvastatin, which is used primarily in the treatment of hyperlipidaemia but which possesses anti-inflammatory properties, might modulate these changes.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin